2011
DOI: 10.2459/jcm.0b013e3283406479
|View full text |Cite
|
Sign up to set email alerts
|

Relation between cardiovascular risk factors and coronary microvascular dysfunction in cardiac syndrome X

Abstract: In CSX patients, both endothelium-dependent and endothelium-independent CMVD cannot be reliably predicted by CVRFs (including serum CRP levels), alone or in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…10 Using this intracoronary thermodilution method, the present study was undertaken to document CMR directly in patients with CSX, and for the first time, we demonstrated direct evidence of CMD in patients with CSX, as represented by the increased IMR and the impaired CFR. Our results about CFR are in agreement with previous reports as mentioned above, [1][2][3] by noninvasive techniques, indicating impaired CFR in patients with CSX. Our findings that severity of myocardial ischemia in these patients is related to thermodilution-derived CFR endorse the results of previous clinical studies 7,19 that DTS can reflect transthoracic CFR in patients with microvascular angina.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…10 Using this intracoronary thermodilution method, the present study was undertaken to document CMR directly in patients with CSX, and for the first time, we demonstrated direct evidence of CMD in patients with CSX, as represented by the increased IMR and the impaired CFR. Our results about CFR are in agreement with previous reports as mentioned above, [1][2][3] by noninvasive techniques, indicating impaired CFR in patients with CSX. Our findings that severity of myocardial ischemia in these patients is related to thermodilution-derived CFR endorse the results of previous clinical studies 7,19 that DTS can reflect transthoracic CFR in patients with microvascular angina.…”
Section: Discussionsupporting
confidence: 83%
“…[1][2][3][4][5][6] The likely pathophysiological mechanism for CSX is suggested to be coronary microvascular dysfunction (CMD), presenting with increased coronary microvascular resistance (CMR) and impaired coronary flow reserve (CFR), thus resulting in myocardial ischemia and subsequent angina pectoris. [1][2][3][4] However, although abnormal CFR or myocardial perfusion defects were demonstrated by transthoracic Doppler echocardiography, 1,2,7 cardiovascular MR, 1,8 and positron emission tomography, 3 the elevated CMR has never been directly documented, and the correlation between CMR and severity of ischemia has not been elucidated in this setting.…”
mentioning
confidence: 99%
“…Other studies failed to show hypertension as an independent predictor of ED in these patients [7]. Thus this relation deserves further investigation in larger studies.…”
mentioning
confidence: 87%
“…Indeed, CRP levels were previously found increased in CSX patients, and were also shown to correlate with systemic ED and with endotheliumdependent CMVD [4][5][6]. Notably, in a recent study we found that CRP levels were the only independent predictor of endothelium-independent CMVD in a group of CSX patients [7].…”
mentioning
confidence: 99%
“…The suggested normal range for CFVR has varied over the past years [38,39]. CMD was first defined with a cutoff point of 2.5, which then changed to 2.0 [16,40,41].…”
Section: Discussionmentioning
confidence: 99%